(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ismail AS, Rizal Y, Kasim A. 2021. Identification of bioactive compounds in gambier (Uncaria gambir) liquid by-product in West Sumatra, Indonesia. Biodiversitas 22: 1474-1480. Gambier liquid by-product (GLB) is a by-product of gambier production, alleged to contain similar flavonoid compounds. Currently, there is no available information on the active components of GLB. This study, therefore, aims to identify the active compounds in GLB using Fourier transform infrared spectroscopy (FTIR), and screen for active compounds using liquid chromatography coupled to quadrupled the mass spectrometry time of flight (LC-MS/MS QTOF) positive (ESI+) and negative (ESI-) ionization modes. The results of the functional-group identification spectra showed 5 peaks, and the GLB was characterized by a hydroxyl group (OH) at 3423.22 cm-1 wavelength, indicating a phenolic compound. Meanwhile, CO2 was identified at 2360.92 and 2344.84, C=O at 1654.43 and C-H stretching at 1400.26 cm-1 wavelength. LC-MS/MS screening in ESI+ mode identified that the GLB contained 22 active compounds, while the ESI- mode confirmed that the GLB had 14 active compounds. Based on these two ionization modes, nine compounds, quercetin 3-glucoside, gallocatechin-4beta-OI, (-)-epi-afzelechin, quercetin-3-O-(2G-?-Lrhamnosyl)-rutinoside, kaempferol-3-O-?-rutinoside, quercetin-3-O-?-L-rhamnoside, epigallocatechin 3-O-P-coumarate, quercetin 3-O-(6’’-acetyl-galactoside) 7-O-rhamnoside and quercetin 3-(4’’-acetylrhamnoside) 7-rhamnoside were discovered. Therefore, GLB was discovered to contain 27 active compounds that all of these compounds are flavonoid group, and some of these substances are also present in the gambier product.